The effect of mercury ions on the metabolic activity of Poecilia Reticulata cells - Aleksey Afonin; LN Komarova; ER Lyapunova (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2023)
Among anthropogenic factors polluting ecosystems and affecting living organisms, mercury, and its compounds are the most toxic. In this study, we investigated the effect of mercury ions on freshwater live-bearing fish Poecilia reticulata. The cytotoxicity of mercury was analyzed on Poecilia reticulata fry using the MTT test. Studies have shown that small concentrations of mercury can have a stimulating effect on the metabolic activity of fish cells, but at high concentrations, the mercury had a depressing effect.